Graphene oxide catalyzed ketone α-alkylation with alkenes: enhancement of graphene oxide activity by hydrogen bonding. Issue 37 (17th April 2019) - Meng, Guangrong; Patel, Mehulkumar; Luo, Feixiang; Li, Qingdong; Flach, Carol; Mendelsohn, Richard; Garfunkel, Eric; He, Huixin; Szostak, Michal
Abstract : The first ketone-alkylation using olefins and alcohols as simple alkylating agents catalyzed by graphene oxide is reported. Extensive studies of the graphene surface suggest a pathway involving dual activation of both coupling partners. Abstract : Direct α-alkylation of carbonyl compounds represents a fundamental bond forming transformation in organic synthesis. We report the first ketone-alkylation using olefins and alcohols as simple alkylating agents catalyzed by graphene oxide. Extensive studies of the graphene surface suggest a pathway involving dual activation of both coupling partners. Notably, we show that polar functional groups have a stabilizing effect on the GO surface, which results in a net enhancement of the catalytic activity. The method represents the first alkylation of carbonyl compounds using graphenes, which opens the door for the development of an array of protocols for ketone functionalization employing common carbonyl building blocks and readily available graphenes.